Central VEGF-A pathway plays a key role in the development of trigeminal neuropathic pain in rats - Lee, Geun W (Mol Pain, 2019)
The study reported here investigated the role of the central vascular endothelial growth factor-A (VEGF-A) pathway in the development of trigeminal neuropathic pain following nerve injury. A Sprague-Dawley rat model of trigeminal neuropathic pain was produced using malpositioned dental implants. The left mandibular second molar was extracted under anesthesia and replaced with a miniature dental implant to induce injury to the inferior alveolar nerve. The inferior alveolar nerve injury produced a significant upregulation of astrocytic VEGF-A expression in the medullary dorsal horn. The nerve injury-induced mechanical allodynia was inhibited by an intracisternal infusion of VEGF-A(164) antibody. Although both VEGF-A Receptor 1 (VEGF-A R1; colocalized with the blood–brain barrier) and VEGF-A Receptor 2 (VEGF-A R2; colocalized with astrocytes) participated in the development of trigeminal neuropathic pain following nerve injury, only the intracisternal infusion of a VEGF-A R1 antibody, and not that of a VEGF-A R2 antibody, inhibited the increased blood–brain barrier permeability produced by nerve injury. Finally, we confirmed the participation of the central VEGF-A pathway in the development of trigeminal neuropathic pain by reducing VEGF-A expression using VEGF-A(164) siRNA. This suppression of VEGF-A produced significant prolonged anti-allodynic effects. These results suggest that the central VEGF-A pathway plays a key role in the development of trigeminal neuropathic pain following nerve injury through two separate pathways: VEGF-A R1 and VEGF-A R2. Hence, a blockade of the central VEGF-A pathway provides a new therapeutic avenue for the treatment of trigeminal neuropathic pain.